Coverage of science, technology, engineering and mathematics (STEM) initiative in tertiary institutions.:the herald and daily news. - Gono, Ozwell (Midlands State University, 2019)
The research explored the coverage of Zimbabwe’s STEM initiative in tertiary institutions by The Herald and Daily News how each newspaper was reporting the government’s initiative at higher and tertiary level. The polarized content produced by the two newspapers was taken into considerations as this was influenced by the different ownership patterns of the two newspapers. The study which is qualitative in nature used archival research as a method of data collection. Through content analysis and Critical Discourse Analysis (CDA), it was established that owners of the newspapers and advertisers are involved in the process of content creation at The Herald and Daily News through their financial and political power. The provision of revenue in terms of advertisements to the two newspapers automatically gives power to the advertisers to determine how the STEM initiative should be framed to the readers. Those in control influence their newspapers what to write and how they represent the government’s progress on STEM initiative in tertiary institutions. The Herald controlled by the government which is the ruling party ZANU PF would frame the government spearheading the STEM initiative only in a positive way while Daily News, a private anti-government newspaper would criticise the government exposing their failures in spearheading the STEM initiative. There is need for the two newspapers to give more coverage of STEM at tertiary level and not just primary and secondary giving absolute fair coverage and reporting without the influence of ownership control.